Modelling of Ca-looping for a 250 MWe Lignite Coal Fired Power Plant. (July 2017) - Hrdlicka, Jan; Opatril, Jan; Vodicka, Matej; Skopec, Pavel; Pilar, Lukas
Abstract: This paper presents a model of a Ca-looping CCS system that is applied on a reference conventional lignite coal fired power plant. The gross electric power output of the reference plant is 250 MWe, with coal consumption 214 t/h and corresponding CO2 production 211 t/h. The Ca-looping system is considered as a retrofit of this power plant. The general model of the power plant balance is connected with a detailed model of the Ca-looping system, consisting of two separated models of carbonator and calciner. The model of a circulating fluidized bed type carbonator is the main part of the model and includes modelling of the fluidized bed hydrodynamics and the chemistry of the CO2 reaction with the limestone sorbent. Two cases for 71 and 87% CO2 capture are modelled. The outputs of the model show material flows and energy inputs and outputs of the Ca-looping system and dimensions of the calciner in the Ca-L system. Generally, required thermal power input for the Ca-looping system integrated is about 50-70% of the power input of the original power plant, offering about 300 MW thermal power that is utilizable for additional electricity production.